Toxicity of sediments from the Stang Alar watershed (Brest) assessed by a battery of bioassays - Naudin, Sabine; Pardos, M.; Quiniou, Françoise (CCSD, 1995)
[Departement_IRSTEA]GMA [TR1_IRSTEA]GMA3-Altérations physico-chimiques et biologiques des écosystèmes d'eau courante National audience The toxicity of sediment samples taken along two streams of the Stang Alar watershed (under miscellaneous contaminations) was evaluated by several acute and chronic bioassays with freshwater and seawater organisms. Freshwater assays concerned the photosynthetic activity of an algal monoculture Selenastrum capricornutum and a natural phytoplankton community of lake Geneva, the survival of the cladoceran Daphnia magna and the embryolarval development of a fish Brachydanio rerio. Seawater assays were the Microtox test with the bacteria Photobacterium phosphoreum and an oyster Crassostrea gigas embryo stage test. The sediments of the main stream showed a high contamination by lead and zinc aswell as a greater toxicity compared to its tributary (under a low non-point source pollution). The toxicity was greater when the organisms were exposed to whole sediments compared to water extracts. The Microtox test lead to the better sensitivity and discriminatory ability among the different bioassays. La toxicité de sédiments provenant de deux ruisseaux du bassin versant du Stang Alar, exposés à diverses contaminations, a été testée par un ensemble de bioessais aigus et chroniques en eau douce et en eau de mer. Les tests en eau douce ont porté sur l'activité photosynthétique d'une culture d'algue Selenastrum capricornutum et d'une communauté de phytoplanctons du lac Léman, la survie du cladocère Daphnia magna, le développement embryo-larvaire du poisson Brachydanio rerio. En eau de mer, l'activité bioluminescente de la bactérie Photobacterium phosphoreum a été suivie, ainsi que le développement embryonnaire de l'huître Crassostrea gigas. Les sédiments du ruisseau principal se révèlent plus contaminés par le plomb et le zinc et plus toxiques que ceux de son affluent (soumis à une pollution diffuse modérée). Les essais réalisés avec les sédiments entiers témoignent d'une plus forte ...